Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Melalui Disiplin Kerja pada Pegawai Rutan Kelas II B Bantaeng - Jarimuddin Jarimuddin; Gunawan Gunawan; Bahtiar Maddatuang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine the impact of training and work motivation on employee performance, with work discipline acting as an intermediary variable that mediates the influence of both variables on employee performance. This study uses a quantitative method with a descriptive design to gain a deep understanding of the relationship between these variables. The research sample consisted of all 49 employees of the Class II B Bantaeng Detention Center, selected using a saturated sampling technique, where all employees served as respondents. Data were collected through field observations and a questionnaire using a five-point Likert scale, which included questions regarding training, work motivation, work discipline, and employee performance. This questionnaire was designed to measure respondents' perceptions of the factors that influence their performance, as well as the relationship between the variables of training, motivation, work discipline, and employee performance. After the data were collected, an analysis was conducted using path analysis to identify the direct and indirect influences between the variables involved in the research model. The results showed that training and work motivation have a positive and significant influence on work discipline. This means that the better the training provided to employees, and the higher their level of work motivation, the better the employee's work discipline will be. Furthermore, good work discipline has a direct effect on improving employee performance. In other words, work discipline acts as a mediator that strengthens the relationship between training, motivation, and employee performance. These findings confirm that non-technical factors such as training and work motivation play a significant role in improving employee performance by enhancing their work discipline. This study provides important insights into the importance of effective training and high motivation to foster good work discipline, which in turn can improve employee performance.